2020
DOI: 10.1200/go.20.00032
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukemia: Real-World Data From India

Abstract: PURPOSE Chronic lymphocytic leukemia (CLL) is uncommon in India. There are limited studies on CLL from the Indian subcontinent. METHODS This was a prospective study (2011-2017) of consecutively diagnosed patients with CLL at a single center. The diagnosis, prognosis, treatment indication, response criteria, and adverse events were recorded as per International Workshop on Chronic Lymphocytic Leukemia guidelines. Biosimilar rituximab dosing (375 mg/m2) was fixed for all cycles. Time to next treatment (TTNT) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 21 publications
1
32
1
Order By: Relevance
“…Whether clinically indicated dose reductions impact clinical outcomes has been debatable in several recent studies [13,14]. The median PFS in our study (14 months) was much shorter than our historical cohort of patients receiving CIT ([ 30 months) and that reported in the real-world data (35 months) [15]. This was due to a combination of factors related to increased rate of infections, deaths, dose reductions, and probably delay in time to initiating ibrutinib.…”
Section: Discussioncontrasting
confidence: 54%
“…Whether clinically indicated dose reductions impact clinical outcomes has been debatable in several recent studies [13,14]. The median PFS in our study (14 months) was much shorter than our historical cohort of patients receiving CIT ([ 30 months) and that reported in the real-world data (35 months) [15]. This was due to a combination of factors related to increased rate of infections, deaths, dose reductions, and probably delay in time to initiating ibrutinib.…”
Section: Discussioncontrasting
confidence: 54%
“…Only patients of the higher SES could afford the ibrutinib option in our study. This is probably the reason for observed less financial difficulty with ibrutinib than CIT though the cost of 1‐month of ibrutinib is the same as the cost of the entire six cycles of CIT 8 . Previous studies have shown significantly low QoL of actively/previously treated patients with CIT compared to those on W&W 3‐5 .…”
Section: Discussionmentioning
confidence: 99%
“…This is probably the reason for observed less financial difficulty with ibrutinib than CIT though the cost of 1-month of ibrutinib is the same as the cost of the entire six cycles of CIT. 8 Previous studies have shown significantly low QoL of actively/previously treated patients with CIT compared to those on W&W. [3][4][5] QoL studies on ibrutinib have so far only been reported from clinical trials and abstract forms. 16,17 The differences in the QoL on ibrutinib and CIT could be because of the different modes of action of the drugs, adverse events, higher SES of patients on ibrutinib, and the convenience of administration.…”
Section: Impact Of Prognosis and Therapy On Qolmentioning
confidence: 99%
See 1 more Smart Citation
“…(invasive infections) in hematological population is at least 10%. Thus, considering only the worldwide cases of acute myeloid leukemia (around 120.000 new cases in 2017), a conservative estimation would be 12,000, but the real burden is higher since other type of patients are at risk [15][16][17].…”
mentioning
confidence: 99%